Sejarah Penanggalan India - Saifullah, Najmuddin; Sukma, Mega (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2022)
The Indian calendar is a complex calendar. The variety of calendars in several regions also adds to its own uniqueness. There are calendars that use the sun as a reference, some use the sun and the moon. This paper discusses the development of the Indian calendar from the earliest times to the present. The method used in this research is qualitative and includes library research. The results obtained are that the Indian calendar has developed and has changed. The Indian calendar is divided into two namely, solar and luni-solar. The luni-solar calendar is further divided into two, namely the amanta and purimanta. The Indian calendar, which uses solar calculations, is divided into two, namely the Sayana year (used by the Indian National Calendar) and the Nirayana Year (used on a zonal basis in certain regions such as the Tamil, Orissa, Malayali, and Bengal calendars).